Comparison between Whatman FTA Elute Cards and Conventional Swab for the Detection of Pathogenic Enteric Bacteria Using an RT-qPCR Assay. (2nd July 2021) - Yue, Na; Jia, Zichao
Abstract : The emergence of outbreaks of foodborne illness is closely associated with food contamination caused by various enteric pathogens, such as Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enterica serovar Enteritidis, and Staphylococcus aureus . The control of enteric pathogens poses a challenge due to the fact that these pathogens can persist for a long period of time in the environment. The rapid detection of pathogenic organisms plays a crucial role in the prevention and identification of crises related to health, safety, and well-being. Improper sample handling and processing may influence the diagnostic efficacy and accuracy. The aim of the present study was to compare the preservation capacity for enteric bacteria between Whatman Flinders Technology Associates (FTA) cards and swabs for reverse transcription-quantitative PCR (RT-qPCR) detection. It was found that Whatman FTA cards exhibited an improved preservation capacity for five types (both laboratory and environmental strains) of enteric bacteria, including Escherichia coli O157:H7, Listeria monocytogenes, Salmonella enterica serovar Enteritidis, and Staphylococcus aureus for RT-qPCR detection. Hence, Whatman FTA cards may be a suitable tool for the routine isolation of foodborne bacteria for molecular diagnosis. Therefore, the use of Whatman FTA cards for sample collection and preservation may increase sensitivity and accuracy for bacteria isolation and diagnosis.